Financial Technology and Strengthening Women's Business in Digital Era: a Digital Sociology Perspective Overview (Case Study of Women Group Partners in the P2P Lending Platform in Babakan Village, Ciseeng District, Bogor Regency) - Damayanti, Elia; Kolopaking, Lala Mulyowibowo; Sjaf, Sofyan (Sodality: Jurnal Sosiologi Pedesaan, 2019)
This study aimed to analyze women who used fintech specialy P2P Lending. Basically, P2P loans provided convenience for women both in providing capital assistance and business development. After all, in reality fintech didn’t have an impact on the development of women's businesses in various countries. The purpose of this study was to identified why fintech didn’t have an impact on the the development of women's business in rural areas. This study was conducted used quantitative methods supported by qualitative data analyze. This study was conducted in Ciseeng District, Bogor Regency, West Java. The results of the study showed that women in Babakan village can’t used technology well, men control family decision-making in majority, business ownership wasn’t a self-owned business;  hungers for money with consumptive culture in loan group. Members have more than one loan, startups are only providers of capital that are not accompanied by training, guidance and business consulting.